2003
DOI: 10.1515/jpm.2003.031
|View full text |Cite
|
Sign up to set email alerts
|

Validity of short term variation (STV) in detection of fetal acidemia

Abstract: In cases < 34 weeks' gestation, STV values below 4.9 msec and 5.1 msec are able to predict umbilical artery pH < 7.0 and PCO2 > 60 mmHg, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 15 publications
1
15
0
5
Order By: Relevance
“…An initial search of 398 citations, identified 7 primary articles 10,11,[22][23][24][25][26] 24 where no such record was found. Five studies were performed on high risk pregnancies 10,11,23,25,26 , one on low-risk 24 and one included both high and low risk populations 22 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial search of 398 citations, identified 7 primary articles 10,11,[22][23][24][25][26] 24 where no such record was found. Five studies were performed on high risk pregnancies 10,11,23,25,26 , one on low-risk 24 and one included both high and low risk populations 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were performed on high risk pregnancies 10,11,23,25,26 , one on low-risk 24 and one included both high and low risk populations 22 . Amongst high-risk pregnancies, 4 studies observed a predictive relationship of STV for neonatal acidaemia in intrauterine growth restricted (IUGR) fetuses 10,11,23,26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STV is the most extensively studied parameter of computerised CTG, showing correlation with the presence of metabolic acidosis (Pincus 1991;Anceschi et al 2003;Serra et al 2008). In general, large variability reflects a healthy ANS and also normal activity of chemoreceptors, baroreceptors and cardiac responsiveness, while a decreased STV is associated with impending deterioration of foetal oxygen supply and finally intrauterine death.…”
Section: Discussionmentioning
confidence: 99%
“…Neuere Studien zeigen, dass bei einer Kurzzeitvariabilität von > 5,1 ms bei Feten vor der 34. SSW kein Nabelschnur-pH < 7,0 zu erwarten ist [11].…”
Section: Diskussionunclassified